UNFAMILIAR WORDS OF MINANGKABAUNESE: A CASE OF CLASSIC MINANGKABAUNESE IN PITARUAH AYAH BY ANGKU YUS DT. PARPATIAH - Fahri Eka Putra; Saunir Saun; Delvi Wahyuni (Universitas Negeri Padang, 2018)
The focus of this research was to find the unfamiliar words of Minangkabaunese in classic Minangkabaunese Advices of “Pitaruah Ayah” by Angku Yus Dt. Parpatiah. The purposes of this research are: (1) To find the unfamiliar words for Minangkabaunese young generations in classic Minangkabaunese advices entitled “Pitaruah Ayah”by Angku Yus Dt. Parpatiah (2) To find the meaning of the unfamiliar words (3) To find the class of words of the unfamiliar words. This research was concern to find the current status of several words in Minangkabaunese which possible to become unfamiliar for its young generations through sampling processes in the district of Nanggalo Kota Padang. From the research 88 unfamiliar words of Miangkabauese were found in classic Minangkabaunese Advices of “Pitaruah Ayah” by Angku Yus Dt. Parpatiah. The most dominant class of words of the unfamiliar words of Minangkabaunese is noun amounted 40.9% of the data. And 48 % of the unfamiliar words were not found in the dictionaries of Minangkabaunese to Indonesian language. Several factors influence the occurrence of the unfamiliar words such as (1) language change of Minangkabaunese (2) The language interference of Indonesian language.